The Protective Effect of Melatonin on Plasma Lipid Profile in Rats with Cerulein-induced Acute Pancreatitis - Ercan Keskin; Deniz Uluışık (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThe objective of this study was to assessment the effect of melatonin on lipid profile in rats with experimentally induced acute pancreatitis. In this study, 32 adult, male, healthy Wistar Abino rats were used. Group I animals was no applied. Group II animals was intraperitoneally administered 50 mg/kg melatonin per rat twice for two hours intervals. Animals of group III received two intraperitoneal injections of cerulein (50 µg/kg and 25 µg/kg bw, respectively) at two hours intervals. Animals of group IV received two intraperitoneal injections of cerulein (50 µg/kg and 25 µg/kg bw, respectively) at two hours intervals and the rats received an intraperitoneal injection of 50 mg/kg melatonin 30 min before each cerulein injection. After 12 hours from the last cerulein injection, total cholesterol, triglyceride, LDL, HDL levels was determined. In this study, experimentally induced acute pancreatitis resulted in significantly increase in levels of total cholesterol, triglyceride and LDL (p lt;0.05), while HDL level significantly decreased compared with control group level (p lt;0.05). Pretreatment of melatonin to the rats with acute pancreatitis importantly reduced triglyceride and LDL levels compared to pancreatitis group (p lt;0.05). In conclusion, melatonin pretreatment may alleviate the abnormalities in plasma lipid profile caused by acute pancreatitis.